2011
DOI: 10.1007/s10668-010-9281-5
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use among smallholder rice farmers in Tanzania

Abstract: In an interview study conducted among smallholder rice farmers in Rufiji, Tanzania coastal mainland, and in Cheju, Zanzibar, farmer's pesticide use and risk awareness were assessed. The farmers generally lacked knowledge or possibilities to manage the pesticides as prescribed by the manufacturers. Few farmers knew what kind of pesticides they were using and had never seen the original packages, as pesticides were usually sold per weight or already diluted without labeling. Protective equipment was rarely used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 24 publications
5
54
0
Order By: Relevance
“…In other words, farmers with knowledge about types of prohibited pesticides and farmers who uphold views towards frequent and massive use of pesticide on generating pesticide residue and massive use of pesticides against the surrounding environment are more likely to overuse pesticides. This finding casts doubts on Stadlinger et al's argument, which proposed that farmers' lack of environmental knowledge and concern is the key factors leading to pesticide overuse [20]. To explain this contradiction, one of the possible reasons is that farmers with the above characteristics are more likely to comply with pesticides application instructions and recommended doses, nevertheless, following the instructions and recommended doses may lead to pesticide overuse.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In other words, farmers with knowledge about types of prohibited pesticides and farmers who uphold views towards frequent and massive use of pesticide on generating pesticide residue and massive use of pesticides against the surrounding environment are more likely to overuse pesticides. This finding casts doubts on Stadlinger et al's argument, which proposed that farmers' lack of environmental knowledge and concern is the key factors leading to pesticide overuse [20]. To explain this contradiction, one of the possible reasons is that farmers with the above characteristics are more likely to comply with pesticides application instructions and recommended doses, nevertheless, following the instructions and recommended doses may lead to pesticide overuse.…”
Section: Discussionmentioning
confidence: 87%
“…The result indicated that farmers' gender, education background, size of farming, family size and their attitude towards environmental conservation have significant effects on their pesticide use behaviors [18]. Both Abhilash and Singh's and Stadlinger et al's studies found that the lack of professional knowledge and understanding on pesticide use is the key factor attributing to pesticide overuse and misuse [19,20]. A similar finding was presented by Zhao et al, showing that those who: have low education level, fail to acquire pesticide use knowledge and lack understanding on the adverse impact of pesticides, are more likely to apply pesticides with high toxicity [21].…”
Section: Factors Attributing To Pesticide Applicationmentioning
confidence: 99%
“…), with synthetic pesticides often being part of the package to the farmers [82]. This is also exacerbated by the farmers' high concern for access to inputs and the priority placed on these inputs [20] rather than the desire for knowledge or the use of non-chemical pest control methods [92]. This leaves little room for delivery of IPM knowledge packages through various training channels without input incentives.…”
Section: Poor Understanding Of the Ipm Concept And Information Flow Amentioning
confidence: 99%
“…Since Rachel Carson's Silent Spring attention has been given to the hazards of extensive pesticides use in developed and developing countries (e.g. Karlsson 2004;Hoi et al 2013;Ríos-González et al 2013;Jansen and Dubois 2014), including sub-Saharan Africa (Ngowi et al 2007;Jansen and Harmsen 2011;Stadlinger et al 2011;Kateregga 2012;Macharia et al 2013;Mengistie et al 2014).…”
Section: Introductionmentioning
confidence: 99%